Perilaku Perawatan Luka Perinium, Pola Hidup Sehat dan Kondisi Kesehatan Ibu Post Partum Masa Pandemi Covid-19 - Islah Wahyuni (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
The pandemic covid-19 needs to be an effort to handle infection prevention for mothers and infants. Infection in pregnancy accounts for 11% of the causes maternal morbidity, the most vulnerable period for infection is in the puerperium or after delivery. One of the factors that facilitate infection is wound the birth canal. It can be a pathway for microorganisms. A healthy lifestyle is also a factor influencing the healing of perineal wounds. There is a relationship between of knowledge, nutrition, exercise and personal hygiene. Perineal injury requires time to heal for 2-3 weeks and it takes good care of the perineal wound to avoid infection. The purpose of the study was to identify the behavior of perineal Wound Care, Healthy Lifestyle and post partum maternal health conditions during the Covid-19 Pandemic at BPM Islah Wahyuni. The sample of 30 respondents were post partum on March 10 to June 25, 2020. The results obtained from the Behavioral Care of Perineal Injury both 27 respondents 90%, Healing Time <3 weeks 20 respondents (80%), PerinealInfection 0%, conditions physically healthy (96.7%). Post partum mothers should maintain perineal wound care, promote health and preventing transmission of post partum infection during this pandemic covid-19.